Faktor yang Memengaruhi Kualitas Informasi Laporan Keuangan Pemerintah Daerah Kota Bandar Lampung - Wulandari, Wulandari; Nurdiawansyah, Nurdiawansyah (Jurnal EMT KITA, 2026)
The purpose of this study was to determine the effect of Human Resource Competence, Application of Government Accounting Standards, and Government Internal Control on the Information Quality of Regional Government Financial Reports in Bandar Lampung City. A total of 36 samples were used in the data collection process which involved distributing questionnaires via Google from to the Regional Work Unit (SKPD) in the Bandar Lampung City Government office. The data analysis method used was multiple linear regression analysis which included validity, reliability, assumption tests. classical, and hypothesis testing. Processed with Statistical Pruduct and Service Solution version 17. The results showed that Human Resource Competence had a positive and significant effect on the Quality of Financial Report Information for the Regional Government of Bandar Lampung City. Application of Government Accounting Standards has a positive and significant effect on the Information Quality of Regional Government Financial Reports of Bandar Lampung City. Government Internal Control has a positive and significant effect on the Information Quality of the Regional Government Financial Reports of Bandar Lampung City.
Keywords: Competency of Human Resources; Government Accounting Standards; Government Internal Supervision; LKPD Information Quality